A platelet P-selectin test predicts adverse cardiovascular events in patients with acute coronary syndromes treated with aspirin and clopidogrel. (December 2014) - Thomas, Mark R.; Wijeyeratne, Yanushi D.; May, Jane A.; Johnson, Andrew; Heptinstall, Stan; Fox, Susan C.
Abstract There is wide variation in response to antiplatelet therapy and high on-treatment platelet reactivity is associated with adverse cardiovascular events. The objective here was to determine whether the results of a novel strategy for assessing platelet reactivity (based on P-selectin measurement) are associated with clinical outcomes in patients with acute coronary syndromes (ACS). This was a prospective cohort study of 100 ACS patients taking aspirin and clopidogrel. P-selectin tests designed to assess response to P2Y12 antagonists or aspirin were performed alongside light transmission aggregometry. For the P2Y12 P-selectin test, an optimal cutoff for high platelet reactivity was determined by receiver operating characteristic (ROC) curve analysis. Patients were divided into two cohorts based on this value: patients with (n = 42) or without (n = 58) high platelet reactivity. The primary endpoint was defined as the composite of cardiovascular death, myocardial infarction and stent thrombosis. After 12 months, the primary endpoint occurred in 12 patients. ROC curve analysis determined that the P2Y12 P-selectin test results were predictive of the primary endpoint (area under curve = 0.69, p = 0.046). The primary endpoint occurred more frequently in patients with high on-treatment platelet reactivity compared to those without (21.4% vs. 5.2%; hazard ratio (HR) 4.14; p = 0.026). The P2Y12 P-selectin test results correlated with light transmission aggregometry (Spearman p < 0.0001). Using the Aspirin P-selectin test, only two patients demonstrated high on-treatment platelet reactivity. This study suggests that a P2Y12 P-selectin test is capable of detecting high on-treatment platelet reactivity, which is associated with subsequent cardiovascular events.